Spin Nernst effect and intrinsic magnetization in two-dimensional Dirac materials - Gusynin, V.P.; Sharapov, S.G.; Varlamov, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
We begin with a brief description of the role of the Nernst–Ettingshausen effect in the studies of the high-temperature superconductors and Dirac materials such as graphene. The theoretical analysis of the NE effect is involved because the standard Kubo formalism has to be modified by the presence of magnetization currents in order to satisfy the third law of thermodynamics. A new generation of the low-buckled Dirac materials is expected to have a strong spin Nernst effect that represents the spintronics analog of the NE effect. These Dirac materials can be considered as made of two independent electron subsystems of the two-component gapped Dirac fermions. For each subsystem the gap breaks a time-reversal symmetry and thus plays a role of an effective magnetic field. We explicitly demonstrate how the correct thermoelectric coefficient emerges both by the explicit calculation of the magnetization and by a formal cancelation in the modified Kubo formula. We conclude by showing that the nontrivial dependences of the spin Nersnt signal on the carrier concentration and electric field applied are expected in silicene and other low-buckled Dirac materials.